Gastroprotective action of Quertulyne in rats with toxic hepatitis - A. A. Petrenko; A. P. Levitsky (Kazimierz Wielki University, 2016)
Petrenko A. A., Levitsky A. P. Gastroprotective action of Quertulyne in rats with toxic hepatitis. Journal of Education, Health and Sport. 2016;6(12):866-874. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.254426 http://ojs.ukw.edu.pl/index.php/johs/article/view/4186         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016.   UDC  616.33+342.092   GASTROPROTECTIVE ACTION OF QUERTULYNE IN RATS WITH TOXIC HEPATITIS   A. A. Petrenko, A. P. Levitsky   SE «The Institute of Stomatology and Maxillo-Facial Surgery of the NAMS of Ukraine» Odessa, Ukraine flavan@mail.ru   Summary Aim: To investigate of gastroprotective action of Quertulyne in rats with toxic hepatitis. Materials and methods: The toxic hepatitis was reproduced in rats by hydrazine sulphate. Quertulyne (quercetine + inulin + citrate Ca) introduced per os in dose of 300 mg/kg during 14 days. The state of gastric mucosa was determined by the levels of biochemical markers of inflammation (MDA, elastase), the degree of microbial contamination (urease), index of non-specific immunity (lysozyme), antioxidant defence (catalase, index API), hepatitis existence was determined by the serum levels of liver markers (bilirubine, ALT, alkaline phosphatase). The dysbiosis degree was calculated by relation urease and lysozyme. Results: The levels of liver markers and the degree of dysbiosis in serum was increased at hepatitis. After introducing of Quertulyne these indices were reduced to nearly norm. The levels of inflammation markers and urease were raised into mucosa of stomach of rats with hepatitis. After in traducing of Quertulyne the indices were reduced to norm. The conclusion: The toxic hepatitis develop gastritis, which may be prevent by Quertulyne. Key words: hepatitis, stomach, gastritis, Quertulyne, enzymes.